Os novos papéis e funções da cidade média de Caruaru - PE: uma análise a partir da expansão do ensino superior - Valença, Mariana Rabêlo (2018)
Caruaru plays a role of intermediation in the Pernambuco´s urban network and its place has been resignified by the consumption boom and by the consumers´ profile changes, driven by regional growth, through the enlargement of clothing production and correlate activities. With such changes, there is a geographic scales´ movement that points to inter-space interactions. In the current globalization context, higher education has a relevant role in the knowledge incorporation to territory and to production. In the last decades, the Brazilian State engendered the basis for higher education´s enlargement, beyond the major urban centers, provoking change-over in receptor cities´ urbanization, including medium-sizes cities and its regions. On this, we raise a few questions: How do a specialized service, such as higher education, potentializes and is potentialized by a city´s centrality? What is the place for medium-sizes cities in the university expansion process? How do the higher education contributes to cities and regions´ economic´s promotion? Our aim is to comprehend the higher education institutions´ role in the urban and city restructure and the inter-space interactions due to it. Our hypothesis is that there is a role and function alteration performed by Caruaru and its region from the higher education´s expansion in the 2000s, as well as a social-economic promotion, explained by the inter-space interactions´ establishment. The agents´ articulation and the political-institutional arrangements constitute selective spaces, as a way and a product from the political-economical strategies. A knowledge producer territory and innovation support has been constituted from the new higher education institutions´ installation, besides the innovative structures because of its intermediation condition in the urban network, allowing that Caruaru and its region articulate with wider scales, inserting them in the scope of globalization. However even more, we see the strengthening of horizontalities, by allowing a scientific, innovative and technologic contribution for spaces that saw itself geographical and economical farway. Therefore, in our perspective, Caruaru is a city of ―territorial responsibility‖, that enables the enlargement of citizenship exercise. The development of the work consisted in the construction of theoretical and methodological references, mainly concerning to medium-sizes cities, inter-space interactions, urban heterchy, horizontalities and verticalities, and fieldwork to acquire data and information about Caruaru and its region, for questionnaires application and interviews conduction.